2008
DOI: 10.1016/j.eeh.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Scylla and Charybdis. Explaining Europe’s exit from gold, January 1928–December 1936

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…4 Under the exchange rate system of the interwar gold standard, countries attempted to balance the stability of the system with rising domestic pressures. Eichengreen (1992) and Simmons (1993), and more recently Wandschneider (2008) and Wolf (2008) have shown that the changing political landscape after World War I increased the pressure to orient monetary policy more towards domestic economic goals. If governments were willing to leave the gold standard, and would let the exchange rate depreciate, they would not be forced to compress domestic spending.…”
Section: Some Background On the Interwar Periodmentioning
confidence: 99%
“…4 Under the exchange rate system of the interwar gold standard, countries attempted to balance the stability of the system with rising domestic pressures. Eichengreen (1992) and Simmons (1993), and more recently Wandschneider (2008) and Wolf (2008) have shown that the changing political landscape after World War I increased the pressure to orient monetary policy more towards domestic economic goals. If governments were willing to leave the gold standard, and would let the exchange rate depreciate, they would not be forced to compress domestic spending.…”
Section: Some Background On the Interwar Periodmentioning
confidence: 99%
“…The Gold Bloc countries stayed depressed, while the countries leaving gold early recovered by 1935 (Eichengreen and Sachs, 1985;Campa, 1990;Bernanke and James, 1991;Eichen-green, 1992). The main determinants for the timing of abandoning the gold parity were deflationary pressure, the existence of banking crises, the gold cover ratio, and the extent of trade integration (Wolf, 2007(Wolf, , 2008 Finally, we detect a severe degree of price rigidity of the Swiss economy during the Interwar Period, which impeded an internal adjustment and therefore also contributed to a prolonged recession. • Demand Functions:…”
Section: Conlusionmentioning
confidence: 99%
“…Given the size of this commitment, the weak position of the Austrian economy, and difficulties over the negotiation of international assistance, the crisis turned into a currency crisis of the Schilling, which then spread to Hungary. A different set of events that was ultimately linked to the issue of reparations, led in July 1931 to a crisis in Germany that looked like a "twin crisis" with a near simultaneous run on bank deposits and the currency (Schnabel 2004 Wolf (2008). The literature on currency crisis that distinguishes between first, second and third generation models gives a useful guidance to understand this curious pattern and to explore systematically the pressures that European countries on the gold-standard faced in the 1930s.…”
Section: The Shadow Of World War Onementioning
confidence: 99%
“…Especially capital importers were put between Scylla and Charybdis who in an attempt to defend their parity and access to foreign capital, put massive deflationary pressure on their economies (Wolf 2008). Real wages and real interest rates soared, resulting in mass unemployment and a sharp decline in manufacturing output and investment.…”
mentioning
confidence: 99%